Who’s Getting Cited: Representation of Women and Non-White Scholars in Major American Criminology and Criminal Justice Journals Between 1986-2005 - Kim, Bitna; Hawkins, Paul M. (International Journal of Criminology and Sociology, 2013)
This article presents findings from an ongoing study of the integration of women and non-white scholarship into the discipline of criminology and criminal justice. The most-cited women and non-white scholars in six major American journals were determined for 1986–2005 to investigate (1) if the dissemination of published research findings in criminology and criminal justice (CCJ) is affected by gender and race/ethnicity and (2) if changes in scholarly influence of women and non-white scholars in CCJ over 20 years exists. A number of explanations are suggested to account for gender and racial differentials in citation rates.